PENGGUNAAN SERAT TANDAN KOSONG SAWIT DALAM PENINGKATAN KEKUATAN PADA BETON BERSERAT - Henny Lydiasari; Ari Yusman Manalu; Rahmi Karolina (Jurnal Penelitian Kelapa Sawit, 2017)
The potency of oil palm empty fruit bunches (OPEFB) fibers as one of the by-products of processing oil palm is increasing significantly so that proper management is needed in reducing environmental impact. One of the utilization of OPEFB fibers is as a substitution material in construction which usually the material is derived from non-renewable mining materials so that the number is increasingly limited. Therefore, it is necessary to study to know the performance of OPEFB fiber in making construction products especially concrete. In this case, the experiment was conducted using experimental method with variation of fiber addition by 0%, 10%, 15%, 20%, 25%, and 30%. Each specimen was tested by weight, slump value, compressive strength, tensile strength, elasticity and crack length. As the results, the variation of fibers addition by 10%, decrease of slump value is 7%, concrete weight is 3% and crack length is 8% while increase of the compressive strength is 2.7% and the modulus of elasticity is 33.3% but its tensile strength decreased insignificantly by 0.05% . Furthermore, the addition of fibers above 10% to 30% decreased compressive strength is still below 10% and tensile strength below 2% while the weight of concrete, slump value and crack length decreased. Therefore, the addition of 10% can replace the performance of concrete without fiber but the addition of above 10% can still be used on non-structural concrete.